Penguatan Kualitas Pendidikan Melalui Pendekatan Partisipatif Dalam Pengajaran Dan Pembelajaran Di Desa Rumah Gerat Kec. Sibiru-Biru - Hebron Pardede; Anisa Berti Tua Ambarita; Efriani Sinaga; Yolanda Clarissa Angelin; Tita Artasari Simanullang (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The Community Service Program (PKM) aims to improve the quality of education in Desa Rumah Gerat, Kecamatan Si Biru-Biru, through a participatory approach to teaching and learning. The participatory approach involves students, and the community as active participants in the learning process. The PKM program was conducted from February 3 to 29, 2024, using various learning methods that involve information technology. The results of the program showed an increase in reading and numeracy skills in Kindergarten (TK), Elementary School (SD), and Junior High School (SMP) students after the tutoring program. This program is expected to help students in Desa Rumah Gerat obtain better education and contribute to village development